Learning Cell-Type-Specific Gene Regulation Mechanisms by Multi-Attention Based Deep Learning With Regulatory Latent Space - Kang, Minji; Lee, Sangseon; Lee, Dohoon; Kim, Sun (Frontiers in Genetics, 2020)
Epigenetic gene regulation is a major control mechanism of gene expression. Most of the existing methods for modeling the control mechanism of gene expression used only a single epigenetic marker and few methods were successful in modeling the complex mechanisms of gene regulations using multiple epigenetic markers on transcriptional regulation. In this paper, we propose a Multi-Attention based deep learning model to integrate multiple markers and understand gene regulation mechanisms. In experiments with 18 cell line multi-omics data, the proposed model predicted the gene expression level more accurately than the state-of-the-art model. Moreover, the model successfully revealed the cell-type-specific gene expression control mechanisms. Finally, the model identified genes enriched for specific cell types in terms of their functions and epigenetic regulation.